DIGGING UP NON-ENGLISH TEACHERS’ PERSPECTIVES ON THEIR STUDENTS’ ESP NEEDS - Dewi Nur Widiyati; Risa Arroyyani (INOVISH JOURNAL, 2022)
This study aims to identify and explore non-English teachers' perspectives on their students' ESP needs. This study is a descriptive study with a qualitative approach. The participants in this study were 16 public health lecturers at STIKes Surya Global Yogyakarta. A semi-structured questionnaire was distributed to participants to gather information related to their needs. The study analyzes the data from closed questions using simple statistics and from open questions using interpretations. The results showed that the importance of learning English is to support students’ academic fields and their communication skills. Reading is a basic skill that needs to be mastered. The students found it difficult to write English journal abstracts, practice oral communication, read, comprehend, and review academic sources in English. Teachers sometimes use English in the form of resources including books written in English and international journals and websites. Students need to learn English during their study period and after graduation. The topics needed to learn to support students’ backgrounds were health technology, health business service management, web causation of disease, health insurance, abstract, environmental health, health information system, safety, health promotion, epidemiology triangle, iceberg phenomenon of disease, research design epidemiology, epidemic, and infectious diseases, wastewater treatment, hygiene, and sanitation.Keywords: Students’ needs, ESP, public health students